PEMANFAATAN MEDIA 3 DIMENSI UNTUK MEMPERMUDAH PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VI PADA MATERI BANGUN RUANG - Tri Ratna Dewi; Resti Septikasari; Sri Enggar Kencana Dewi; Imam Rodin (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
The task of a teacher is not only to abort the obligation to teach but rather how to deliver teaching materials that can be understood by students. A teacher must be creative, innovative in choosing to sort out the use of learning media as a tool to facilitate the delivery of teaching materials so that by utilizing learning media it will make it easier for students to understand the teaching materials/materials delivered. The purpose of this study was to determine whether the students' understanding of mathematical concepts before and after the use of 3D media in the learning process, besides that it also saw the effect of using 3D media on students' understanding of mathematical concepts in spatial building materials. The subject of this research is class VI SDN Marga Jaya with a total of 18 students. This research is an experimental research with One-Group Pretest-Posttes Desig design. Based on the data obtained from the pretest score of 1120. While the ideal score is 1800. Thus, the value of students before the application of 3-dimensional media is 1120: 1800 = 0.62 = 62% of the expected. Furthermore, the value obtained from the posttest results is 317. The total ideal score is 360. Thus, the calculated score obtained from the posttest scores collected is 317: 360 = 0.88 = 88% of the expected. From the results of these calculations, it can be seen that the value of sig 0.000 < 0.05, which means that there is an influence between the use of 3 dimensional media on the understanding of mathematical concepts of fourth grade students in building materials at SDN Marga Jaya.